Test and Numerical Study on Monotonic Behavior of Complex CFT Column Joints - Zeliang Yu; Bin Yang; Bin Jia; Yuhong Yan; Shaowen Xiao; Ke Lei (Advances in Civil Engineering)
This paper presents a test and numerical investigation into the monotonic behavior of three different complex steel trusses to concrete-filled tubular (CFT) column joints. Based on an engineering structure, 1 : 4 reduced-scale specimens are manufactured and the three-dimensional subassembly testing system is designed to apply the monotonic load. Test phenomena and load-stress curves show that all three types of joints have a considerable load-carrying capacity and joint rigidity. Finite element (FE) analysis is adopted, and the stress distribution shows good agreement with test data. Both test and FE results show that local buckling and yielding in the root region of steel truss are the main failure modes of test joints and the core area of the CFT column remains intact which are in accordance with the design conception of “strong column and weak beam.” Design conception of proposed overlap joint form is then investigated based on the FE model, and results show that the optimized overlap joint can effectively reduce the stress concentration in the adjacent steel tube and beam member when compared to the traditional N-type overlap joint. Finally, the influence of the outer diaphragm on the stiffness of joint is analyzed. By comparing the end-displacement of the beam member, conclusion can be obtained that the beam flange thickness is suggested to be chosen as the outer diaphragm thickness. The forms of three different proposed joints and their design conceptions can provide good guidance for designers and engineers.